EFEK SUSPENSI PENGAWET TERHADAP KUALITAS BUNGA POTONG HERBRAS - Farida Iriani (Jurnal Agroekoteknologi, 2010)
ABSTRACTThe usage of preservative solution as a force to improve the quality of Transvaal daisy cut flower  Ornella cultivar is effective. A preservative that was formulated from sucrose + citric acid + lysol + oxyacetate acid was made as suspension by adding of cmc, will be examined its effectivity in this experiment. An experiment by using Randomized Block Design bifactor, which are dosage of suspension and suspension saving period before it was going to be added into the soaking water of Transvaal daisy cut flower. Respons of variable which analyzed are vase life, petal blooming capacity, dynamics of fresh weight relative and water absorpsiton relative 2-days. The result showed that dosage a 50 mLL-1 of suspension and three months saving period was the best compare to another respons variable.Keywords: Cut flower preservative, Dosage suspension